Gambaran Status Tekanan Darah Penderita Hipertensi di Desa Karanganyar Kecamatan Kalianget Kabupaten Sumenep - Emdat Suprayitno; Cory Nelia Damayanti; Mujib Hannan (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2019)
ABSTRACT Hypertension is a health problem in the world, especially in developing countries. Hypertension is often called a silent killer (silent killer) because it is included in a deadly disease without accompanied by symptoms first as a warning for victims. The problem of high hypertension, especially in the elderly with concomitant decline in organ function. This type of research is quantitative descriptive using non-analytic cross sectional design. The sampling technique used was total sampling with a sample size of 32 people. The instrument used in the form of a tensimeter and blood pressure observation sheet. The results showed that the majority of respondents aged 55-60 years were 10 people (31.25%), the majority of respondents were male as many as 18 people (56.25%). Blood pressure status in patients with hypertension in Karanganyar village is systolic blood pressure 140-159 mmHg, diastolic blood pressure 90-99 mmHg as many as 18 people (56.25%) It can be concluded that the majority of blood pressure status of hypertension sufferers in Gadung Hamlet, Karanganyar Village, Kalianget Subdistrict are in the category of Hypertension. Keywords: Blood Pressure, Hypertension